The Glazing for the Stairs in the Refurbished Margherita Theatre in Livorno - Vincenzo Mamone (Challenging Glass Conference, 2018)
The paper illustrates the design project of the main laminated glass balustrade of a steel staircase installed in the historical Margherita Theatre in Livorno, Italy. After its final closure, almost 15 years ago, the new owners decided to refurbish the building and to convert it into a shopping center. The entire project was developed with particular attention to the conservation of the building style. In order to join the ground level to the former gallery level a new steel staircase has been placed and three laminated glass balustrades were added. The bigger one is a big rectangular glazing 4047 long and 5765 mm high consisting of 8 rectangular laminated glass panels, each composed of two 12 thick fully tempered glass sheets laminated with PVB interlayer. Unique steel connections were designed and built in order to join the glass panels to each other and to the steel staircase. The connections to the staircase were designed so to avoid the out-of-plane movements of the glass panels, and to allow the free vertical relative movement between staircase and glass. The horizontal out-of-plane movements of the top edge of the big glazing is prevented owing to a horizontal 5600 mm long laminated glass fin. The paper illustrates the design and check of the glass panels, their geometry and functioning, the numerical analyses and the results.